PENGARUH KEPUASAN DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT BINA ARTHA VENTURA AREA SUKABUMI: Manajemen sumberdaya manusia - REKA ARDIAN DAN RIDA JUNITA (Ekonomedia, 2020)
This study aims to find out how the Satisfaction, Training and Employee Work Productivity level and determine the effect of Satisfaction, Training on Employee Productivity at PT Bina Artha Ventura. This study uses a type of survey research methods, namely research conducted in large and small populations, but the data studied are samples taken from these populations, to find relationships between variables. With sampling all employees as many as 33 employees. The analytical method used is the validity test, reliability test, classic assumption test, correlation analysis, determinant coefficient and multiple regression tests, and hypothesis testing using SPSS 24.0. The results of this study stated that the Satisfaction and Training at PT Bina Artha Ventura was already good because the majority of respondents' answers from each indicator variable were agreed and strongly agreed. Employee satisfaction affects productivity with a significance value of 0.007, and based on the results of b1 multiple regression is 0.255. For training variables, there is an influence on employee work productivity with a significance value of 0.000, and the b2 value of multiple regression is 0.453. Satisfaction and Training simultaneously stated influence on Employee Productivity this is based on a significance value of 0,000, and the coefficient of determination of the magnitude of the effect is 81.7%, meaning that 18.3% is influenced by variables outside the Satisfaction and Training variables.